The effects of straw incorporation with plastic film mulch on soil properties and bacterial community structure on the loess plateau - Li, Yüze; Hu, Yingchun; Song, Duanpu; Liang, Shihan; Qin, Xiaoliang; Siddique, Kadambot H. M. (European journal of soil science, 2021)
The application of plastic film mulch and the return and incorporation of crop straw into topsoil as independent treatments affect soil physicochemical properties, including nutrient balance/cycling. It remains unclear whether combining straw incorporation and plastic film mulch significantly affects soil physicochemical properties and bacterial communities. We conducted a two‐factor (plastic film mulch application and maize straw incorporation) randomized block design experiment with four treatments: no plastic film mulch or straw incorporation (C), plastic film mulch (M), straw incorporation without mulch (CS) and straw incorporation with mulch (MS). Soil was sampled at the end of the growing cycle after 3 years of treatment. Soil organic carbon (SOC), total nitrogen (TN) and nitrate‐nitrogen (NO3−‐N) concentrations significantly improved after straw incorporation. Plastic film mulch had a significant negative effect on soil bacterial richness, whereas straw incorporation had no effect. Straw incorporation had a significant positive effect on bacterial diversity, whereas plastic film mulch had no effect. The MS and M treatments had significantly more Proteobacteria than the C and CS treatments. Formation of the soil bacterial community structure was driven by soil TN, NO3−‐N and SOC in the treatments with straw incorporation, and soil ammonium‐nitrogen (NH4+‐N) in the treatments without straw incorporation. In conclusion, plastic film mulch coupled with straw incorporation can significantly change the taxonomical and functional composition of soil bacterial communities and enhance soil bacterial diversity by affecting carbon and nitrogen cycling in cropland soils of farmland, especially in arid and semiarid regions. Highlights SOC, TN and NO3−–N concentrations significantly improved after straw incorporation Straw incorporation had a greater effect on bacterial communities than plastic film mulch Soil bacterial community structure was driven by soil TN, NO3−–N and SOC after straw incorporation Soil bacterial community structure was driven by soil NH4+‐N without straw incorporation.